The relative role of glacial refugia and longstanding barriers in the diversification of a fossorial squamate. Issue 5 (3rd July 2020) - Almeida, João P. F. A.; Thomé, Maria Tereza C.; Sturaro, Marcelo J.; Pereira, Ricardo J.; Mott, Tamí
Abstract : The Neotropics host the highest number of species of the biological realms, but the roles of Pleistocene climatic oscillations and longstanding geographic barriers on the origins of this remarkable biodiversity remains debated. Here, we test the relative contribution of these evolutionary mechanisms on the genetic and phenotypic diversification of Amphisbaena pretrei, a poorly studied amphisbaenid from eastern Brazil. Ecological niche modelling identified a large area along the coast of north-eastern Brazil that remained climatically stable since the last glacial maximum (21 kyr). Morphological analysis revealed the existence of differentiation in the southernmost sampled locality, despite generalized morphometric conservatism. Genetic structure was organized into two clades that are separated by the São Francisco river and that diverged some 3 Myr, before the recent Pleistocene glacial cycles. Coalescent analyses rejected all scenarios that included demographic changes, supporting instead diversification under population stability, also confirmed by neutrality tests. Taken together, our results support a prominent role of the São Francisco river as a longstanding barrier favouring the diversification of the fossorial A. pretrei, relative to recent Pleistocenic demographic dynamics. Generally, this study shows that including species with diverse natural histories is necessary before attempting any generalization regarding the evolutionary processes underlying Neotropical biodiversity.